Occupational employment projections to 2012. - Hecker, Daniel E.; Frank, David S. (Monthly Labor Review, 2004)
Employment in professional and related and in service occupations are expected to increase the fastest and add the most jobs from 2002 to 2012, while office and administrative support occupations should grow about half as fast as the total; production occupations should grow very slowly